Kanoniczny wymiar ekonomicznej troski o dobra kościelne. Pieniądze w Kościele - Wenz, Wiesław (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
The Canonical dimension of economic well-being for the material goods of the Catholic Church. Money in the Church. The Canonical dimension of economic well-being for the material goods of the Catholic Church.is realized by fulfilling faithfully the intentions of the Catholic Church’s lawmaker, regardless of the secular authority, that, base on the natural law, the Church has the right to acquire material goods, govern and manage them and also to alienate them. However, the reason for having material goods is to use them according to the relevant objectives of the mission of the church. The legislator said that the objectives of the Catholic Church are mainly: the divine worship, ensuring providing sufficiently for the social security of clerics and other church workers, as well as keeping the apostolate and works of charity, especially towards the poor and the misfortune (CJC, 1254§1-2; 1274§1-2).
Keywords: concern for the poor; church worker; the church; the pastor